Ecowomanism, religion, and ecology - Harris, Melanie L., 1975- (Religious Studies, Theology and Philosophy E-Books Online, Collection 2017, ISBN: 9789004328082., 2017)
Ecowomanism emerges from third wave womanist thought that emphasises interdisciplinary, interreligious and intergenerational dialogue as approaches to environmental ethics. Ecowomanism unashamedly validates the importance of the perspectives of women of color, and especially the voices, perspectives and contributions of women of African descent.